2015
DOI: 10.4314/jasem.v18i4.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fungal Filtrates on Seed Germination and Leaf Anatomy of Maize Seedlings (<i>Zea mays</i> L., Poaceae)

Abstract: This study was carried out to investigate the effects of 7-day-old fungal filtrates of Aspergillus niger and Penicillium chrysogenum isolated from maize seeds on percentage germination, morphological and anatomical structures of maize seedlings. The seeds were soaked in culture filtrate of each fungus for 12hrs before planting. Blotter method was used to observe seed germination. Results showed that the percentage germination of the seeds treated with culture filtrates of A. niger and P. chrysogenum (65.33% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
6
8
0
1
Order By: Relevance
“…It could be due to the ability of the fungus to produce Aflatoxins. These findings are consistent with previous findings (Garuba et al, 2014;Jeswal, 1987;Tewfik et al, 1974) that concluded that Aflatoxins prevent or reduce the rate of germination of many crop seeds. It reduces the growth of the crop seedling as well as the development of the radicles and coleoptiles produced from irrigated grains.…”
Section: Effect Of Fungal Filtrates On Germination Rate Of Wheat Graisupporting
confidence: 93%
See 3 more Smart Citations
“…It could be due to the ability of the fungus to produce Aflatoxins. These findings are consistent with previous findings (Garuba et al, 2014;Jeswal, 1987;Tewfik et al, 1974) that concluded that Aflatoxins prevent or reduce the rate of germination of many crop seeds. It reduces the growth of the crop seedling as well as the development of the radicles and coleoptiles produced from irrigated grains.…”
Section: Effect Of Fungal Filtrates On Germination Rate Of Wheat Graisupporting
confidence: 93%
“…filtrate showed (43.5% ± 19.9, 43.2% ± 1.5, 36.0% ± 4.4 and 29.9% ± 4.7) reduction of the coleoptile lengths after three, five, seven and ten days respectively. These results are consistent with the finding of the previous study (Garuba et al, 2014). This study showed 65.33% and 79.67% germination ratio of corn seeds due to the effect of A. niger and Penicillium chrysogenum filtrates, respectively, when compared with control.…”
Section: Effect Of Fungal Filtrates On Germination Rate Of Wheat Graisupporting
confidence: 93%
See 2 more Smart Citations
“…Pathogenic fungi are known to produce mycotoxins which can penetrate seed coats, endosperm and cotyledon [27]. In a study on the examination of the effects of 7-day-old fungal filtrates of Penicillium chrysogenum and Aspergillus niger isolated from maize seeds on the morphology and percentage germination of maize seeds soaked in culture filtrates before planting on blotters, the results showed that the percentage germination of the seeds treated with culture filtrates of the fungi were significantly lower than that of the control [28].…”
Section: Protective Potential Of the Extracts Against Pathogensmentioning
confidence: 99%